IL-21: The Future of Medicine - Syed Raza Shah; Muhammad Ahmed Jangda; Mohammad Danial Yaqub; Ayesha Altaf Jangda; Maham Khan; Brian Tomkins (Journal of Clinical and Diagnostic Research, 2017)
Interleukin-21 (IL-21), a T- cell-derived cytokine, is a signaling molecule secreted by a subpopulation of T cells called follicular T helper (Tfh) cells. Studies have proved that IL-21 co-stimulates T cell proliferation by mediating enhanced T cell viability. This is done when IL-21 binds to its receptor, activating the phosphatidylinositol-3 kinase (PI-3K) signaling pathway and inducing B-cell Lymphoma-2 (Bcl-2) expression. Besides the B and T cells, IL-21 also regulates several Natural Killer (NK) cell functions. Due to its multi-faceted effects on different receptors, IL-21 has been used in multiple diseases. However, it was recently found that IL-21 had potent effect on various viruses including Lymphocytic Choriomeningitis Virus (LCMV), influenza virus and Vesicular Stomatitis Virus (VSV). The study proved that both B and CD4+ T cells need IL-21 signaling for generating long-term humoural immunity by generating long-lived plasma cells, thus, highlighting the importance of IL-21 in humoural immunity to viruses. These findings highlight how IL-21 could be important in the development of antiviral vaccines and vaccines for other potential life-threatening diseases leading scientists to design future vaccines to incorporate IL-21 directly or to use the ability to stimulate IL-21 as a gauge of vaccine activity. It is the need of the hour to go for larger studies which will be needed to better elucidate the cause and effect relationship and to demonstrate the effect size. It may possibly yield appreciable results in the future for untreatable diseases like HIV/AIDS.